Classification and Methodology of National Movement Games Training Physical Qualitie - Nurullaev Abdukhamid Ruzimbaevich; M.A.Ruzimbaev (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses the types of national action games that nurture physical qualities and each type of game that nurtures physical qualities.